2017
DOI: 10.5152/eurasianjmed.2017.16129
|View full text |Cite
|
Sign up to set email alerts
|

What is the Importance of Body Composition in Obesity-related Depression?

Abstract: Objective: It is known that depression is common in obese individuals. Besides the effects of obesity, pathogenic effects of increase in visceral and abdominal fat mass on depression are also being investigated. Our study aimed to show the relationship between visceral fat percentage detected with practical methods and the presence and severity of depression.Materials and Methods: Our study included 104 obese patients and 50 healthy controls. In all individuals, the severity of depression was assessed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
(37 reference statements)
0
14
0
2
Order By: Relevance
“…However, the results were controversial between western countries and China. Some studies conducted in western countries reported that obesity was associated with increased depression prevalence [7][8][9]. There were also some systematic review indicating that obesity increase the risks of depression [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results were controversial between western countries and China. Some studies conducted in western countries reported that obesity was associated with increased depression prevalence [7][8][9]. There were also some systematic review indicating that obesity increase the risks of depression [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Em relação à CC, um estudo realizado com idosos mostrou associação significativa entre depressão e medidas de CC elevadas 39 . Também se investigou a relação entre % de gordura e gravidade da depressão, encontrando que em pacientes com depressão a CC, circunferência do quadril, % de gordura corporal e de gordura visceral foram significativamente maiores do que aqueles sem depressão 40 .…”
Section: Discussionunclassified
“…Hasil penelitian ini, sejalan dengan penelitian yang dilakukan oleh Koksal, dkk. tahun 2017 dan Inandia tahun 2012 yang menemukan hubungan antara persen lemak tubuh dengan indeks massa tubuh (30,11). Hubungan antara persen lemak tubuh dengan status gizi dalam penelitian ini, dapat menjadi indikasi bahwa persentase lemak tubuh merupakan indikator yang cukup baik dalam menggambarkan status gizi pegawai di UPN "Veteran" Jakarta.…”
Section: Hubungan Persen Lemak Tubuh Dengan Status Giziunclassified